Polish Commodity Exchanges in the Years 1946-1951. An Outline of the Problem - Macyra, Roman (Studia Historiae Oeconomicae, 2006)
The end of the war was at the same time the beginning of the reconstruction of companies and organisational structures of the country's economic life, and such was at least the conviction of many pre-war entrepreneurs and activists in the field of economy, who were returning to their positions. However, the enormity of war destruction, lack of information on the fate of the owners of companies during the war and instability of the political situation were not conducive to the fast reconstruction of the economic base, all this in spite of the appeals of the authorities. New political authorities of the state through a number of feigned activities, suggesting their wish to preserve political and economic pluralism, however, undertook a determined effort to subjugate and captivate the society whose "condition" as has been observed by Krystyna Kersten, "... after the war lasting six years and after two occupations had a very significant influence on its attitudes and behaviour towards the new order established by communists, and these attitudes and behaviours meaningfully influenced the tactics and methods used by the camp which took power."